A Rapid and Convenient Microwave-Promoted Synthesis of 3,5-Disubstituted 2-Chloropyridines and Their Conversion into Tetrazolo[1,5-a]pyridines - Gogoi, Shyamalee; Gogoi, Sanjib; Boruah, Romesh C. (Synthesis, 2013)
This work describes a rapid and convenient synthesis of 3,5-disubstituted 2-chloropyridines from various α,β-unsaturated ketoximes utilizing the Vilsmeier reaction under microwave irradiation. The 3,5-disubstituted 2-chloropyridines were further converted into tetrazolo[1,5-a]pyridines by a microwave-mediated solid-phase reaction. The products were isolated in good yields within a very short reaction time.
Keywords: 2-chloropyridine; Vilsmeier reaction; tetrazolo[1,5-a]pyridine; microwave